Mitochondrial Metabolism in the Intestinal Stem Cell Niche—Sensing and Signaling in Health and Disease - Urbauer, Elisabeth; Rath, Eva; Haller, Dirk (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial metabolism, dynamics, and stress responses in the intestinal stem cell niche play a pivotal role in regulating intestinal epithelial cell homeostasis, including self-renewal and differentiation. In addition, mitochondria are increasingly recognized for their involvement in sensing the metabolic environment and their capability of integrating host and microbial-derived signals. Gastrointestinal diseases such as inflammatory bowel diseases and colorectal cancer are characterized by alterations of intestinal stemness, the microbial milieu and mitochondrial metabolism. Thus, mitochondrial function emerges at the interface of determining health and disease and failure to adapt mitochondrial function to environmental cues potentially results in aberrant tissue responses. A mechanistic understanding of the underlying role of mitochondrial fitness in intestinal pathologies is still in its infancy, and therapies targeting mitochondrial (dys)function are currently lacking. This review discusses mitochondrial signaling and metabolism in intestinal stem cells and Paneth cells as critical junction translating host- and microbe-derived signals into epithelial responses. Consequently, we propose mitochondrial fitness as a hallmark for intestinal epithelial cell plasticity, determining the regenerative capacity of the epithelium.